Advances in child development and behavior. - Kail, Robert V. (Advances in child development and behavior, 2008)
Volume 36 of the Advances in Child Development and Behavior series includes ten chapters that highlight some of the most recent research in developmental and educational psychology. A wide array of topics are discussed in detail, including King Solomon's Take on Word Learning, Orthographic Learning, Attachment and Affect Regulation, Function, Family Dynamics, Rational Thought, Childhood Aggression, Social Cognitive Neuroscience of Infancy, Children's Thinking, and Remote Transfer in Children, and much more. Each chapter provides in depth discussions of various developmental psychology specializations. This volume serves as an invaluable resource for psychology researchers and advanced psychology students. *Goes in depth to address eight different developmental and educational psychology topics *A necessary resource for both psychology researchers and students.